Pinkalicious and the flower fairy - Kann, Victoria (New York, NY : Harper, an imprint of Harper Collins Publishers, 2019)
"Pinkalicious is absolutely positive that a flower fairy will visit her garden. After all, flower fairies love pink, and so does Pinkalicious! When Pinkalicious transforms her garden into a pink wonderland, will it entice the flower fairy to visit?"--Publisher's description.
Ages 4-8.
Keywords: Fairies -- Juvenile fiction; Gardening -- Juvenile fiction; Girls -- Juvenile fiction